USM-FAU GERMANY ENHANCING COLLABORATION ON DIVERSITY IN EDUCATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 8 September 2016 Universiti Sains Malaysia (USM) through School of Educational Studies is enhancing its collaboration with the FriedrichAlexander Universitat from Erlangen Nurnberg, Germany on "Pupils' Diversity and Integration in Education" after a successful organisation of the USMFAU Conference 2016 here at USM, held from 68 September 2016.